Study of effect of topical mometasone with intralesional platelet-rich plasma versus topical mometasone alone in the treatment of alopecia areata - Kulhari, Monika; Adil, Mohammad; Varshney, Iti; Amin, Syed Suhail (International Journal of Research in Dermatology, 2023)
Background: Alopecia areata (AA) is an autoimmune disorder and exhibits non scarring alopecia. Currently, there is no definitive cure, platelet rich plasma (PRP) has emerged as a newer modality for non-cicatricial alopecias such as AA. This study was conducted to compare the efficacy and adverse effects of topical mometasone with PRP versus topical mometasone alone in the treatment of patients of AA. Methods: This study was conducted on a total of 100 clinically diagnosed cases of AA. Patients in group A were subjected to intradermal injection of autologous PRP every 3 weeks along with topical mometasone cream 0.1% daily for 12 weeks. Group B was treated with topical mometasone cream 0.1% once a day locally over affected site for 12 weeks. Results: Baseline SALT score of group A was 6.05±5.36 while that of group B was 6.62±4.39. The mean SALT score of group A declined to 0.94±1.69 and that of group B 2.19±1.76 over a period of 20 weeks. Excellent response was observed by 12 and 5 patients of group A and group B respectively. Minor side effects like pain was seen in 10 patients (20%) in group A, while atrophy was seen in 2 patients of group B. Conclusions: This is the first ever study evaluating the additional benefit of intralesional PRP. In this study, it was found that adding intralesional PRP with topical mometasone 0.1% cream has higher efficacy and early improvement than topical mometasone alone, in the treatment of AA.